2018
DOI: 10.1155/2018/3258383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novelα-Amylase from Antarctic Sea Ice BacteriumPseudoalteromonassp. M175 and Its Primary Application in Detergent

Abstract: A novel cold-adapted and salt-tolerant α-amylase gene (amy175) from Antarctic sea ice bacterium Pseudoalteromonas sp. M175 was successfully cloned and expressed. The open reading frame (ORF) of amy175 had 1722 bp encoding a protein of 573 amino acids residues. Multiple alignments indicated Amy175 had seven highly conserved sequences and the putative catalytic triad (Asp244, Glu286, and Asp372). It was the first identified member of GH13_36 subfamily which contained QPDLN in the CSR V. The recombinant enzyme (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…M175 has been isolated from Antarctic sea ice, which is a common source of cold-stable alpha-amylase. 27 The microorganisms produce cold-active amylases that have a flexible polypeptide chain to make an easier accommodation of substrates at the low-temperature condition. Also, the enzymes contain lipid composition to maintain greater membrane fluidity.…”
Section: Alpha-amylase Production In Microbial Sourcementioning
confidence: 99%
“…M175 has been isolated from Antarctic sea ice, which is a common source of cold-stable alpha-amylase. 27 The microorganisms produce cold-active amylases that have a flexible polypeptide chain to make an easier accommodation of substrates at the low-temperature condition. Also, the enzymes contain lipid composition to maintain greater membrane fluidity.…”
Section: Alpha-amylase Production In Microbial Sourcementioning
confidence: 99%
“…When the wild-type α-amylase wtAmy175 from Pseudoalteromonas sp. M175 was expressed and studied, the optimum temperature and pH for enzyme activity were found as 30 °C and 7.5, respectively [82]. The enzyme also showed high activity and remarkable stability in 0-10 mM sodium dodecyl sulphate suggesting its capability as an outstanding candidate in detergent and textile industries [83].…”
Section: Strategies To Improve Stability During Cold Adaptationmentioning
confidence: 96%
“…In 2018, a novel α-amylase-producing strain Pseudoalteromonas sp. M175 (KU726544) was identified from Antarctic ice cover by Wang et al [82] and the α-amylase gene amy175 isolated from this microbe was cloned and expressed in E. coli. By analysing the characteristics of the expressed enzyme, it was concluded that the α-amylase gene amy175 could be used as a novel α-amylase source for industrial application with highest activity at 25 °C and pH 8.0, exhibiting the extreme salt-resistance [82].…”
Section: Strategies To Improve Stability During Cold Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…A cold-adapted α-amylases from the Antarctic sea-ice bacterium Pseudoalteromonas sp. M175 exhibited resistance towards all the tested commercial detergents and was shown to improve their stain removal efficiency [93]. Heat-labile α-amylases displaying high activity at low temperature isolated from bacteria of Antarctic seawater were structurally studied [96,97].…”
Section: Cold-adapted Enzymes and Their Biotechnological Applicationsmentioning
confidence: 99%